Determinants of Primary School Teacher Resilience in Papua - Petrus, Simon (IJORER : International Journal of Recent Educational Research, 2026)
Objective: Papua Province has the lowest education index nationally and lags significantly in educational services compared to other regions of Indonesia. To improve educational outcomes, Papua urgently needs high-quality teachers. This study aims to identify the determinant factors of teacher resilience, a key capability that enables school leaders, teachers, and other educational stakeholders to recover and grow from adversity. Method: A random sampling survey was conducted involving 341 public and private primary school teachers in Papua, specifically in Mimika Regency. Data were collected using a structured questionnaire and analyzed with Structural Equation Modeling using Partial Least Squares (SEM-PLS) to determine the relationships among the variables. Results: The study found that spiritual, emotional, and social intelligence significantly influence the teaching motivation of primary school teachers in Mimika, Papua. Motivation, in turn, strongly enhances teacher resilience. Emotional and social intelligence were shown to directly and indirectly strengthen resilience, whereas spiritual intelligence did not have a direct effect on resilience. This finding is particularly significant, as it suggests that spirituality alone does not automatically translate into resilience; instead, its influence is realized only through motivation. In other words, teachers with higher spiritual intelligence become more resilient only when their sense of meaning and purpose is transformed into motivational drive. This highlights the central role of motivation as the psychological mechanism linking multiple intelligences to resilience. Novelty: This study offers a novel perspective by examining how a combination of multiple intelligences—spiritual, emotional, and social—interact with teaching motivation to influence teacher resilience in one of the most underdeveloped education regions in Indonesia. By emphasizing the indirect role of spiritual intelligence, the study not only advances theoretical understanding but also underscores the complexity of building resilient teacher communities in challenging educational environments like Papua.